Event-Triggered H-Infinity Controller Design of Nonlinear Networked Cascade Control System - Zhaoping Du; Jiashuo Bi; Xiaofei Yang; Jianzhen Li (IEEE Access, 2021)
Nonlinearity is ubiquitous in practical industrial production, so this paper investigates the problems of modeling, $H_{∞ }$ control and stabilization for a class of nonlinear networked cascade control systems (NCCSs) under an event-triggered scheme, which makes the system have more practical application value. Firstly, aiming at a kind of typical nonlinear system in industrial production, a new mathematical model is established by adding networked cascade control system and event-triggered scheme. The collaborative design method of primary and secondary controller parameters and event-triggered parameters is completed utilizing linear matrix inequality (LMI). Secondly, based on ensuring its stability, combined with $H_{∞ }$ control, the system’s disturbance is suppressed, making the system more universal. Finally, the feasibility and effectiveness of the proposed method in the nonlinear networked cascade control system has verified by a marine boiler liquid level cascade control system.